An Exemplar Interprofessional Academic Emergency Nurse Practitioner Program: A Blueprint for Success. (January 2017) - Evans, Dian Dowling; Ashooh, Meredith Pollock; Kimble, Laura P.; Heilpern, Katherine L.
Abstract : Emergency department census rates and manpower gaps have continued to rise over the past decade, creating a demand for well-prepared emergency nurse practitioners (ENPs). The implementation of the consensus model for advanced practice nurses has brought acknowledgment by leading health care, physician, and nursing organizations of the ENP specialty as critical to building a high-quality emergency care workforce. Recognition of the ENP's unique skill set, and therefore need of specialty certification, has led to a growing interest in the expansion of nurse practitioner curricula in emergency care. This article describes a novel approach for ENP education based on an interprofessional training model, with an in-depth discussion of curriculum development and clinical placement, as well as program outcomes and implications.